How Motivation mediated Science Achievement of Indonesian Students: a Path Analysis on PISA 2018 data - Candra Putri Nur Cahyani; Ezra Putranda Setiawan (Jurnal Penelitian Pendidikan IPA, 2024)
The low science achievement of Indonesian students in PISA 2018 is still a challenge for Indonesian education stakeholders. For a long time, socio-economic conditions, low interest in reading, and low motivation have often been the causes of these achievements. This study aims to examine the effects of socio-economic status, reading habits, and gender on Indonesian students' science achievements in PISA 2018. To represent the motivation variable, teacher support, parental support, and self-efficacy are placed as mediating variables toward science achievements. Using the path analysis mediation model implemented in R statistical software, we find that economic-social and cultural status, reading habits, and gender have a direct impact on students' science achievement. In addition, socio-economic and cultural status indirectly affects students' science achievement, mediated by teacher support, parental support, and self-efficacy. Reading habits indirectly affect students' science achievement, mediated by teacher support, parental support, and self-efficacy. Last, gender indirectly affects students' science achievement, mediated by parental support and self-efficacy, but does not affect students' scientific literacy scores when mediated by teacher support. Overall, gender has an indirect effect on students' science achievement.